Validity and Practicality of a Science Worksheet Integrating Boranan Dance to Train Scientific Literacy on Equilibrium Material - Hanan Zaki Alhusni; Utama Alan Deta; Binar Kurnia Prahani; Titin Sunarti (Mitra Edukasi dan Publikasi, 2026)
Physics learning in schools can foster essential skills for the current era, one of which is scientific literacy. Scientific literacy involves examining phenomena in students’ everyday lives, which can be explored through local wisdom. However, there are still limited studies that integrate local wisdom into physics learning to develop students’ scientific literacy. Addressing this gap, the present study aims to develop a student worksheet (LKS) integrated with the local wisdom of the Boranan Lamongan dance to enhance students’ scientific literacy. This research describes the feasibility of the developed worksheet in terms of its validity and practicality. The study employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The worksheet was tested on a limited scale in class XI science students at an Islamic Senior High School in East Java. The results show that the integration of local wisdom is feasible for use in physics learning to promote scientific literacy. The validity aspect achieved a PoA score of 84.13% (very valid), while the practicality aspect, assessed through learning implementation, obtained an average score of 96.04% (very practical). Overall, the findings indicate that the student worksheet integrating the Boranan Lamongan dance is feasible as a learning medium to foster students’ scientific literacy. Furthermore, this research contributes to the preservation of local culture by incorporating the Boranan dance into physics education.